TRANSFORMATIONAL LEADERSHIP AND INNOVATIVE WORK BEHAVIOR: A SYSTEMATIC REVIEW - S. Bhatia, Harpreet (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This systematic study examines the link between transformational leadership and innovative behavior, consolidating results from research cataloged in the Scopus database. The review seeks to elucidate the impact of transformational leadership on employees' creativity, problem-solving skills, and overall innovation in firms. Following an extensive search and selection procedure, pertinent publications were analyzed, emphasizing the influence of transformational leadership on cultivating an atmosphere that promotes creativity. The results emphasize critical elements, such as leadership conduct, communication, and motivational tactics that foster creative results. This review delineates both direct and indirect paths by which transformational leadership fosters innovative behavior, so facilitating organizational development and adaptation. It also examines moderating factors such as corporate culture and individual characteristics, providing insights for practitioners seeking to foster a culture of innovation. The assessment finishes by proposing recommendations for future research avenues at the nexus of leadership and innovation.